PERTEMPURAN LAUT ARU: TONGGAK AWAL PENANAMAN JIWA BAHARI DALAM PEMBANGUNAN KEKUATAN MARITIM BANGSA INDONESIA - Sadhyoko, Joseph Army (HUMANIKA, 2015)
Revitalization of the maritime spirit is neccessary for Indonesia people. Battle at the Aru Seawas an historical heritagewhich proved thatthe maritime spirit existed and should be cultivate today. The maritime spiritbecomemental capital for maritime power developmentamong Indonesia people in the future.